Discerning genetic diversity among sunflower germplasm accessions through multivariate analysis - Bana Venkata Ravi Prakash Reddy*, K. Amarnath, B. Chandra Reddy, K. Venkataramanamma, K. Prabhakar and N.C. Venkateswarlu (Electronic Journal of Plant Breeding, 2024)
The objective of the present investigation was to evaluate 135 sunflower germplasm accessions through Principal Component Analysis and Hierarchical cluster analysis to assess the extent of genetic diversity. The principal components with eigen values more than one i.e., PC1 and PC2 describes 38.3% and 21.24% respectively with a cumulative effect of 59.62% of the total variation. The biplot analysis revealed positive association of seed yield per plant for 100 seed weight, head diameter, days to 50% flowering and it was negatively associated with oil content. By using Wards method of clustering, 135 sunflower accessions were aggregated in 12 clusters based on different traits in which cluster VIII includes 30 accessions and is the largest one. The accessions in cluster IV, I and VI had maximum values for 100 seed weight, seed yield per plant and oil content, respectively. The germplasm accessions 213R, 121R, RHA-GPR-110, CMS-107B, IB-11-3, SCG-107, 132R, NGM-15 and OPH-123 were identified to be potential accessions and these can be used for improvement of yield and its attributing traits in sunflower.